ESTIMATION OF OVERPRESSURE BASED ON WIRELINE LOGS IN SUB-BASIN OF JAMBI, SOUTH SUMATRA BASIN - Reulina, Lia
The Jambi Sub-Basin is a sub-basin located in the northern part of South Sumatra Basin. This area is chosen to be the study area because it has indications of the presence of overpressure in forms of thick layer of shale (500 - 13000 feet) and high thermal gradient (2,89 °F/100 ft). The data used in this study are drilling data (direct measurement of pore pressure and final drilling report), wireline log data (log gamma ray, resistivity, density, neutron, and sonic), and supporting data (descriptions of rocks and geochemical data). The purpose of this research is to determine the characteristic of overpressure and to estimate overpressure by using the Eaton method and to determine the distribution of the overpressure zones in the study area. In this research, overpressured intervals can be found in top of the Upper part of Talang Akar, with overpressure mechanism is unloading due to hydrocarbon maturity in well L-1, L-2, L-3, L-4, L-5, and R-1. The result of the correlation of top of overpressure shows that the presence of overpressure has the same pattern with top of the Talang Akar formation. The top of overpressure is shallower to the southeast. The estimation of pore pressure values using Eaton method indicates that the match Eaton’s exponent is 1,5.